Намисто з могильника Острів (за матеріалами досліджень 2017—2020 рр.) - Дяченко, Д.Г. (Археологія і давня історія України, 2022)
Стаття присвячена намистам та їх елементам, виявленим в поховальних комплексах західнобалтського могильника Острів у 2017—2020 рр.
Розглянуто типи й хронологію намистин, особливості намистяного набору. The presence of elements of the necklace sets among
the grave goods is one of the characteristic features of
the Ostriv burial ground. They were found in 21 graves
from 83 excavated in the period of 2017—2020.
In 19 cases they were part of the neck ornament.
The necklace was an attribute of women’s costume in
17 burials, which is slightly less than half of the total
number of women’s burials. This indicates both social
differentiation within the group and differences in
costume composition. Mainly the necklace was found
among the grave goods of girls and young women.
In two cases one shell of Cypraea moneta was found
in men’s burials indicating their use as buttons or talismans.
In total, 546 elements of the necklace set were found
in the burials. Most of the finds (51 %) represented by
glass products, slightly less (45 %) by shells (Cypraea
moneta is absolutely dominated), 3.8 % is non-ferrous
metal products, one detected bead (0.2 %) is made of
faience.
The uneven distribution of elements in the necklace
from one item to almost hundred is recorded. The
number of beads of a certain type in the set could be
large, even absolute, while others consisted of more different
elements but could be inferior to the first one by
total number of copies in the set.
Significant predominance of beads with metal foil,
blue ribbed and Cypraea moneta shells. These varieties
together make up 69 % of all identified elements of the
necklace set and were the most popular and available
for necklace formation among these people.
The marginality of other elements should indicate
their secondary nature and addition to the main set
if possible. However, in our opinion, in this case the
situation is diametrically opposed. The most common
types of elements — with metal foil and Cypraea
moneta — have been obtained by the population in
mass and added to existing vague sets or formed new
ones.